Adventures in opting out : a field guide to leading an intentional life - Flanders, Cait, 1985- (Little, Brown Spark, 2020)
The author offers a trail map to letting go of stories that are no longer serving you, and creating an intentional life that emphasizes the beauty of the natural world, the importance of gaining new perspectives, the joys of real human connection, and the peace that comes from living in harmony with your own values.